Before viewing this page, it would be helpful to learn how to Expand And Factorize Quadratic Expressions.

x^{2} + 7x + 12 = 0

( x + 3 ) ( x + 4 ) = 0

Either ( x + 3 ) or ( x + 4 ) equals zero

If x + 3 = 0 , then x = –3

If x + 4 = 0 , then x = –4

x = –3 or –4

x^{2} + 8x + 12 = 0

( x + 6 ) ( x + 2 ) = 0

Either ( x + 6 ) = 0, or ( x + 2 ) = 0

If x + 6 = 0 , then x = –6

If x + 2 = 0 , then x = –2

x = –2 or –6

2x^{2} – 7x – 15 = 0

( 2x + 3 ) ( x – 5 ) = 0

Either ( 2x + 3 ) = 0, or ( x – 5 ) = 0

If 2x + 3 = 0 , then x = –1.5

If x – 5 = 0 , then x = 5

x = –1.5 or 5

**Q1.** x^{2} – 12x + 35 = 0
**Q2.** x^{2} + 6x – 16 = 0
**Q3.** 3x^{2} – 12 = 0

**Answers**
**A1.** x = 5 or 7
**A2.** x = 2 or –8
**A3.** x = 4